ANALISIS PEMBIAYAAN MURABAHAH PADA PT. BANK SYARIAH MANDIRI KANTOR CABANG PEMBANTU (KCP) PALU TADULAKO - Ansyar, yusniati (Katalogis, 2015)
The aim of this research is too seek and analyze murabahah financing system at PT. Bank Syariah Mandiri, Tadulako Branch Office, Palu. This is aqualitative research in which the respondents selected through purposive sampling method. Data collection methods are participant observation, in depth interviews, documentation, and triangulation. Data analysis technique includes data reductions, data presentation, and conclusions. The result of this study shows that murabahah financing system at PT. Bank Syariah Mandiri, Tadulako branch Office, Palu has been implemented based on laws and requerements in accordance with islamic syariah through murabahah system.